Perfil de no-sensibilidad a antimicrobianos en especies productivas y de compañía de Argentina - Dominguez, Johanna Elizabeth; Maubecin, Elsa; Sánchez Crespo, Rodrigo; Luna, Federico; Petroni, Alejandro; Fernandez Miyakawa, Mariano Enrique (Sociedad Ecuatoriana de Microbiología, 2024)
Poster